Quaternary ammonium compounds - New occupational hazards - Agnieszka Lipińska-Ojrzanowska; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2014)
Quaternary ammonium compounds (QACs, quats) belong to organic ionic chemical agents which display unique properties of both surfactants and disinfectants. Their wide distribution in the work environment and also in private households brings about new occupational hazards. This paper reviews reports about the health effects of QACs. QACs could play a role of sensitizers and irritants to the skin and mucous membranes. It is suspected that particular QACs can display an immunologic crossreactivity between each other and with other chemical compounds containing ammonium ion, such as muscle relaxants widely used in anesthesia. They may promote the development of airway allergy, however, the background mechanisms are still unclear and need to be further investigated. Until now, a few cases of occupational asthma induced by QACs have been described and their involvement in contact dermatitis has been documented. The possibility of anaphylaxis due to QACs cannot be excluded as well. Med Pr 2014;65(5):675-682